Vaccinology in pediatric rheumatology: Past, present and future - Bizjak, Masa; Heshin-Bekenstein, Merav; Jansen, Marc H. A.; Ziv, Amit; Angevare, Saskya; Uziel, Yosef; Wulffraat, Nicolaas M.; Toplak, Natasa; , for the PReS Vaccination Working Party (Frontiers in Pediatrics, 2023)
With the introduction of biological disease-modifying antirheumatic drugs (bDMARDs), the treatment of pediatric patients with autoimmune/inflammatory rheumatic diseases (pedAIIRD) has advanced from the “Stone Age” to modern times, resulting in much better clinical outcomes. However, everything comes with a price, and use of new bDMARDs has resulted in an increased risk of infections. Therefore, preventing infections in pedAIIRD patients is one of the top priorities. The most effective preventive measure against infection is vaccination. The first study on humoral immunity after vaccination in pediatric rheumatology was published in 1974 and on safety in 1993. For many years, data about safety and immunogenicity in pedAIIRD patients were available only for non-live vaccines and the first studies on live-attenuated vaccines in pedAIIRD patients treated with immunosuppressive therapy were available only after 2007. Even today the data are limited, especially for children treated with bDMARDs. Vaccinations with non-live vaccines are nowadays recommended, although their long-term immunogenicity and efficacy in pedAIIRD patients are still under investigation. Vaccinations with live-attenuated vaccines are not universally recommended in immunosuppressed patients. However, measles-mumps-rubella booster and varicella zoster virus vaccination can be considered under specific conditions. Additional research is needed to provide more evidence on safety and immunogenicity, especially regarding live-attenuated vaccines in immunosuppressed patients with pedAIIRD. Due to the limited number of these patients, well-designed, prospective, international studies are needed. Further challenges were presented by the COVID-19 pandemic. This mini review article reviews past and present data and discusses the future of vaccinology in pediatric rheumatology.